1999
DOI: 10.1046/j.1469-8137.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of grass and a dwarf shrub to long‐term changes in soil microbial biomass C, N and P following factorial addition of NPK fertilizer, fungicide and labile carbon to a heath

Abstract: Microbial immobilization may decrease the inorganic nutrient concentrations of the soil to the extent of affecting plant nutrient uptake and growth. We have hypothesized that graminoids with opportunistic nutrient-acquisition strategies are strongly influenced by nutrient limitation imposed by microbes, whereas growth forms such as dwarf shrubs are less affected by the mobilization-immobilization cycles in microbes. By adding NPK fertilizer, labile C (sugar) and fungicide (benomyl) over a 5 yr period in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 46 publications
7
98
2
1
Order By: Relevance
“…Much of the labile C was likely from rhizodeposition (e.g., exudates, mucilages, and lysates) rather than solely from leaching and decomposition of dead root cell soluble contents because root cell soluble concentration alone was not significantly related to microbial biomass. Since soil microbes are usually C limited (Michelsen et al, 1999;Smith and Paul, 1990;Van de Geijn and van Veen, 1993), plant C inputs, especially in the form of labile C such as root exudates, play an important role in supporting microbial biomass and activity (Kuzyakov, 2002), that could further obscure possible C litter chemistry effects on microbial biomass and nonlabile soil C decomposition. One plant species, the forb A. millefolium, showed very high labile C pools that did not correspond to similar increases in microbial biomass C and N, suggesting that this species produced labile C compounds that did not stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the labile C was likely from rhizodeposition (e.g., exudates, mucilages, and lysates) rather than solely from leaching and decomposition of dead root cell soluble contents because root cell soluble concentration alone was not significantly related to microbial biomass. Since soil microbes are usually C limited (Michelsen et al, 1999;Smith and Paul, 1990;Van de Geijn and van Veen, 1993), plant C inputs, especially in the form of labile C such as root exudates, play an important role in supporting microbial biomass and activity (Kuzyakov, 2002), that could further obscure possible C litter chemistry effects on microbial biomass and nonlabile soil C decomposition. One plant species, the forb A. millefolium, showed very high labile C pools that did not correspond to similar increases in microbial biomass C and N, suggesting that this species produced labile C compounds that did not stimulate microbial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Excess 15 N (atom %) was converted to absorption rate of N (in mg N g -1 root DW 2 h -1 ). The total N concentration was also calculated, subtracting the N that had been taken up during the bioassay (Michelsen et al 1999).…”
Section: Nitrogen Uptakementioning
confidence: 99%
“…In nutrient-rich conditions, the dependency of the host plant on mycorrhizal compartment may decrease because it is more cost-efficient to obtain nutrients directly from the soil than via carbon-demanding mycorrhizal fungi (Tuomi et al 2001). In contrast, a number of field studies have also reported fertilization to have no impact on mycorrhizal colonization (Heijne et al 1994;Caporn et al 1995;Michelsen et al 1999;Johansson 2000;Urcelay et al 2003). Soil nutrient availability is also closely associated with soil pH (Kinzel 1983;Eskelinen et al 2009), which, in turn, affects microbial communities (Madigan et al 2003;Högberg et al 2007;Eskelinen et al 2009).…”
Section: Introductionmentioning
confidence: 99%